PdpaMn inhibits fatty acid synthase-mediated glycolysis by down-regulating PI3K/Akt signaling pathway in breast cancer. Issue 10 (November 2020) - Okrah, Eric Achiborebador; Wang, Qiang; Fu, Hexiu; Chen, Qiuyun; Gao, Jing
Abstract : Novel manganese complex, PdpaMn ([(Pdpa)MnCl2]), was developed to induce apoptosis in breast cancer cells. The impact of phosphoinositide-(3)-kinase pathway onto fatty acid synthase (FASN) has an effect on cellular metabolism in breast cancer. However, reverse actions from FASN towards PI3K/Akt are still indefinable. Perhaps, loss of FASN could regulate glycolysis. Previously we established that PdpaMn inhibits FASN and involve in mitochondrial function. This study investigated the activity of PdpaMn on glycolysis and its mechanism. PdpaMn was used to suppress FASN expression in tumor. Expression of ATP and lactic acid level was measured to investigate the glycolysis variance in cells and animals. MCF-7 and 4T1 cells were treated with G28UCM, an inhibitor of FASN and PdpaMn, western blotting to detect PI3K/Akt signaling pathway. The capacity of proliferation was investigated by western blotting and immunohistochemistry. PdpaMn selectively inhibits cancer cells and tumor growth but also block FASN expression and suppresses the content of free fatty acid. Lactate dehydrogenase (LDHA) protein level was down-regulated as G28UCM and PdpaMn inhibited FASN, glucose transporter (Glut1), and pyruvate kinase (PKM2) proteins level were not affected. PI3K, p-Akt in the experimental group evidently declined compared to the control group. Proliferation was suppressed in FASN-arbitrated glycolysis. Our study supports the hypothesis that loss of FASN by PdpaMn suppressed glycolysis via down-regulating PI3K/Akt signaling pathway revealing the direct link between FASN and glycolysis. The results have paved the way to unravel the mechanisms of FASN and mitochondrial will be useful for designing novel co-targeting strategies for breast cancer.